Facile Fabrication of N‐Doped K2Nb2O6 Nanocrystals with Defective Pyrochlore Structure for Improved Visible‐Light Photocatalytic Hydrogen Production. Issue 1 (7th October 2022) - Wang, Jinyuan; Wang, Jinhu; Shi, Run; Zhou, Chao; Zhang, Tierui
Abstract : Semiconductor‐based photocatalytic water splitting is one of the effective ways for future hydrogen (H2 ) production. However, the wide bandgap of most semiconductors severely limits the solar spectral absorption range, which seriously hinders their practical applications. Herein, porous N‐doped K2 Nb2 O6 nanocrystals with defective pyrochlore structure are rationally designed to extend the absorption range from ultraviolet to visible region around 550 nm by NH3 heat treatment. The obtained 6N–K2 Nb2 O6 shows the highest visible‐light activity with an H2 evolution rate of 20.4 μmol h −1  g −1 . More detailed exploration demonstrates that NH3 heat treatment can promote the substitutional nitrogen doping in K2 Nb2 O6 crystals while accompanied by the formation of oxygen vacancies or Nb 4+ species. The hybridization of N 2 p and O 2 p orbitals in the valence band (VB) of the nitrogen‐doped K2 Nb2 O6 makes the VB maximum move more negatively, whereas the conduction band minimum shifted more positively due to the role of defective Nb 4+ species. Such a synergistic effect endows the samples with visible‐light absorption and greatly enhances charge separation and transfer efficiency, resulting in the excellent H2 production performance. This study provides additional insights into the understanding of the effect of nitrogen doping on photocatalysts with excellent visible‐light‐driven photocatalytic activity. Abstract : N‐doped K2 Nb2 O6 nanocrystals with excellent visible‐light response and enhanced photocatalytic hydrogen production activity are synthesized by simple NH3 heat treatment of K2 Nb2 O6 nanocrystals. The higher activity of N‐doped K2 Nb2 O6 is mainly attributed to its appropriate amount of nitrogen doping, leading to excellent visible‐light response and separation and migration efficiency of photogenerated charge carriers.